Self-Medication Pattern among Social Science University Students in Northwest Ethiopia. (16th January 2017) - Gelayee, Dessalegn Asmelashe
Abstract : Background . Inappropriate self-medication causes wastage of resources among others. Method . This survey study was conducted to determine self-medication pattern of 404 social science university students in Northwest Ethiopia, who were selected through stratified random sampling technique. Data were collected using self-administered questionnaire and analyzed with SPSS version 20 statistical software. Binary Logistic Regression analysis was employed withP value < 0.05 considered statistically significant. Result . At 95.3% response rate, mean age of 21.26 ± 1.76 years, and male/female ratio of 1.26, the prevalence of self-medication during the six month recall period was 32.7%. Headache (N = 87, 69.1%) was the primary complaint that prompted the practice and hence analgesics (N = 67, 53.2%) were the mostly used drugs followed by antimicrobials (N = 50, 39.7%). The top two reasons driving the practice were nonseverity of the illness (N = 41, 32.5%) and suggestions from friends (N = 33, 26.2%). Female sex (P = 0.042 ) and higher income (P = 0.044 ) were associated with the practice. Conclusion . Self-medication practice, involving the use of both nonprescription and prescription drugs such as antimicrobials, among the social science university students is high. Therefore health education interventions regarding the risks of inappropriate self-medication are essential.